The Transjugular Intrahepatic Portosystemic Shunt: Technique and Instruments - Keller, Frederick S.; Farsad, Khashayar; Rösch, Josef (Techniques in vascular and interventional radiology, 2016)
Although transjugular intrahepatic portosystemic shunt (TIPS) was first described in 1971, it took 15 more years for technology, in the form of expandable metallic stents, to be developed to make TIPS a viable, widespread clinical procedure. Currently, expanded polytetrafluoroethylene–covered stent grafts that exhibit significantly greater long-term patency are used for TIPS creation by most interventionalists. TIPS creation requires specific interventional skills, tools, and devices for success. In the hands of skillful, experienced interventional radiologists, TIPS creation is performed safely and successfully in greater than 95% of cases.